Are we training junior doctors to respond to major incidents? A survey of doctors in the Wessex region. Issue 5 (25th August 2004) - Madge, S N; Kersey, J P; Murray, G; Murray, J R
Abstract : Objective: To assess the current status of awareness and training of junior medical staff in the Wessex region in the event of a "conventional" major incident. Methods: A telephone questionnaire of specialist registrars (SpRs) (or equivalent, for example, staff grade) in six core specialties was performed in all the 11 acute hospitals in the Wessex region on the same evening. This group was selected to represent a sample of the most senior medical staff "on site" at each hospital. Results: 56 of 64 (87.5%) SpRs participated. Nine of the 56 (16%) SpRs questioned had previously been involved in a major incident, and 18 (32%) had experienced some form of major incident training exercise. Subgroup analysis of the specialties showed that although there were no significant differences in numbers of training experiences between specialties, only one of nine (11%) orthopaedic SpRs had ever been involved in a training exercise. Twenty five of the 56 (45%) SpRs felt that they were confident of their role in the event of an incident. Conclusion: Most middle grade staff in Wessex were not confident of their role in the event of a major incident. Most SpRs questioned had never attended a major incident training exercise.